Facile H2PdCl4-induced photoreforming of insoluble PET waste for C1-C3 compound production - Li, Dani Tong; Yu, He; Huang, Ying (Frontiers in Chemistry, 2023)
Plastic pollution has emerged as a pressing global concern, driven by the extensive production and consumption of plastic, resulting in over 8 billion tons of plastic waste generated to date. Conventional disposal methods have proven inadequate in effectively managing polymer waste, necessitating the exploration of novel techniques. Previous research has demonstrated the successful application of photoreforming (PR) in converting water-soluble oligomer fragments of plastics into valuable chemicals. However, an unresolved challenge remains in dealing with the insoluble oligomer fragments characterized by complex chemical structures and larger molecular sizes. In this study, we propose a facile approach that involves H2PdCl4-induced activation on PET substrate for PR of PET bottles. Remarkably, this method enables the production of C1-C3 compounds without the reliance on sacrificial reagents or photocatalysts. The significant findings of this study offer a practical solution to address the most formidable aspect of plastic PR, specifically targeting the insoluble oligomer fragments. Moreover, this research contributes to the advancement of effective strategies for the sustainable management of plastic waste.